Investigating L2 reading aloud and silent reading in typically developing readers and dyslexic adolescents from grades 6 to 9. (8th September 2021) - Commissaire, Eva; Demont, Elisabeth
Abstract : The goal of this study was to examine the reading performance of French typically developing readers and dyslexic adolescents from grades 6 to 9 in English as a second language (L2) learned in a school context. Lexicality effects and the impact of two sub‐lexical variables, that is cross‐language orthographic markedness and congruency of grapheme‐to‐phoneme correspondences (GPCs), were investigated in three tasks: L2 reading aloud and lexical decision, and L2‐to‐L1 translation. English words and nonwords were divided into three conditions: (a) marked condition in which items have an L2‐specific orthographic pattern (e.g., town ), (b) unmarked congruent condition in which items have an L1/L2 shared orthography and similar GPCs across languages (e.g., fast ) and (c) unmarked incongruent condition that contains incongruent GPCs across languages (e.g., dirt ). The results yielded a significant deficit in dyslexic readers in all three tasks, suggesting poor decoding but also poor lexical orthographic representations in L2 and difficulties in connecting form to semantic representations. This deficit was mostly observed for the unmarked incongruent conditi‐on, highlighting the need to carefully manipulate the sub‐lexical features of items when examining L2 reading. The results are discussed in relation to the cross‐language transfer hypothesis and to mono‐ and bilingual models of reading.